2018
DOI: 10.1039/c8dt00888d
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and zinc complexes bearing NNO-tridentate ketiminate ligands: synthesis, structures and catalysis in the ring-opening polymerization of lactides

Abstract: A series of magnesium and zinc complexes, [(L1-3)2M2(μ-OBn)2] (M = Mg (1-3), Zn (4-6)), have been synthesized by the reaction of NNO-tridentate ketiminate ligands (L1-3-H) and a stoichiometric amount of MgnBu2 (or ZnEt2) and BnOH. In addition, the reaction of these ketiminate ligands (L1-4-H) with a half equivalent of MgnBu2 (or ZnEt2) in toluene provides [M(L1-4)2] (M = Mg (7-10), Zn (11-14)) in good yields. All of these complexes have been fully characterized by NMR spectroscopy and elemental analysis, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 116 publications
3
6
0
Order By: Relevance
“…The TOF values as summarized in Table demonstrate the strong influence of the substitution pattern of the phenoxide substituents on the catalytic activity of the L 1 ‐substituted ( 1 > 2 > 3 > 4 ) and L 2 ‐substituted complexes ( 5 > 6 > 7 > 8 ). The catalytic activity in both groups follows the same trend and was found to increase upon introduction of an electron donating group R at the phenyl ring as was previously reported . Moreover, complexes 1 and 5 containing two methyl substituents in ortho ‐position of the phenoxide ligand are more active than complexes 2 and 6 , which contain two methyl groups in meta ‐position.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The TOF values as summarized in Table demonstrate the strong influence of the substitution pattern of the phenoxide substituents on the catalytic activity of the L 1 ‐substituted ( 1 > 2 > 3 > 4 ) and L 2 ‐substituted complexes ( 5 > 6 > 7 > 8 ). The catalytic activity in both groups follows the same trend and was found to increase upon introduction of an electron donating group R at the phenyl ring as was previously reported . Moreover, complexes 1 and 5 containing two methyl substituents in ortho ‐position of the phenoxide ligand are more active than complexes 2 and 6 , which contain two methyl groups in meta ‐position.…”
Section: Resultssupporting
confidence: 84%
“…reported on magnesium and zinc complexes containing tridentate NNO ‐chelating pyrazoline‐ β ‐ketoiminate ligands with different electron‐donating substituents. These complexes showed high activities towards ROP of LA and produced controlled molecular weight polymers with narrow molecular weight distribution (MWD) . They also found that the metal substituents as well as the electron‐donating substituents of the pyrrolidine‐ β ‐ketoiminate ligands play an important role in the activity and stereoselectivity of the polymerization process.…”
Section: Introductionmentioning
confidence: 98%
“…Each catalyst polymerizes ϵ ‐CL faster (turn over frequencies (TOF) 1090 h −1 1 , 570 h −1 2 , 780 h −1 3 ) than rac ‐LA (TOF 780 h −1 1 , 450 h −1 2 , 570 h −1 3 ) and the catalytic activity in both homopolymerization reactions follow the order 1 > 3 > 2 . The results show that the presence of electron donating t ‐Bu groups (+ I effect) at the ortho and para positions of the imino(phenolate) substituent increases the catalytic activity, whereas electron withdrawing Cl substituents (− I effect) diminish the catalytic activity, confirming the trends recently reported for analogous Me‐substituted complexes L 1–3 2 Ga 4 (Me) 8 [21] and others [22,25,26] . More importantly, the t ‐Bu‐substituted complexes L 1–3 2 Ga 4 ( t ‐Bu) 8 1 – 3 are catalytically more active than the corresponding Me‐substituted derivatives L 1–3 2 Ga 4 Me 8 , [21] most likely due to the higher basicity of t ‐butyl compared to the methyl substituent, which enforces the protonation reaction with BnOH and faster formation of the active (BnO‐substituted) catalyst.…”
Section: Resultssupporting
confidence: 86%
“…Biodegradable polymeric materials derived from renewable and bioderived resources are a potential alternative to petroleum-based plastics. Amongst them, biodegradable polyesters such as polylactide (PLA) and polycaprolactone (PCL) have already found many applications. These polymers are often obtained by ring-opening polymerization (ROP) of cyclic esters catalyzed by organometallic complexes and organocatalysts. However, the design of new biodegradable polyester architectures with improved properties by ROP is seriously restricted by the limited number of commercially available cyclic esters. The development of other catalytic processes for the preparation of a broader range of biodegradable polyesters is necessary.…”
Section: Introductionmentioning
confidence: 99%